Evolutionary and biogeographic history of the black fly Simulium wayani (Diptera: Simuliidae) on the island of Timor - Adler, Peter H.; Takaoka, Hiroyuki; Sofian-Azirun, Mohd; Chen, Chee Dhang; Suana, I. Wayan (Elsevier, 2019)
A recently described species of black fly, Simulium wayani Takaoka and Chen, from the island of Timor was chromosomally mapped to provide insights into its evolutionary and biogeographic history. The morphologically based species status of S. wayani is supported by a suite of fixed chromosomal rearrangements and unique sex chromosomes derived primarily from a large pool of polymorphisms in the S. ornatipes complex in Australia. The banding patterns of its polytene chromosomes indicate that S. wayani is closely related to a pair of homosequential cryptic species (S. norfolkense Dumbleton and S. ornatipes cytoform A2) in the S. ornatipes Skuse complex on mainland Australia; all three species uniquely share the same amplified band in their chromosomal complement. The low level of polymorphism and heterozygosity in S. wayani, relative to Australian populations of the S. ornatipes complex, suggests few colonization events from the larger land mass. © 2019 Elsevier B.V.